If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5x + 7) = 8x + -6 Reorder the terms: 2(7 + 5x) = 8x + -6 (7 * 2 + 5x * 2) = 8x + -6 (14 + 10x) = 8x + -6 Reorder the terms: 14 + 10x = -6 + 8x Solving 14 + 10x = -6 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 14 + 10x + -8x = -6 + 8x + -8x Combine like terms: 10x + -8x = 2x 14 + 2x = -6 + 8x + -8x Combine like terms: 8x + -8x = 0 14 + 2x = -6 + 0 14 + 2x = -6 Add '-14' to each side of the equation. 14 + -14 + 2x = -6 + -14 Combine like terms: 14 + -14 = 0 0 + 2x = -6 + -14 2x = -6 + -14 Combine like terms: -6 + -14 = -20 2x = -20 Divide each side by '2'. x = -10 Simplifying x = -10
| -5(9y+4)= | | 45x^2+90x+25=0 | | 100/370=h/740 | | 0.2x+1.5=0.1 | | 5/15=12/n | | 35x^2+67x+30=0 | | 6x+12y=36 | | 84-5x=40+24 | | 5/n=25/35 | | 6/7=n/35 | | -117-7x=8x++18 | | s=68-20log(0+1) | | 9w-18=48 | | s(t)=68-20log(0+1) | | 8x+24=28 | | 7+11i/i | | 6x+6-5x-7=27 | | 6x+6=5x-7 | | 6x+6+27=5x-7 | | -5(3z+4)-z-27= | | 4x^3(x-3)= | | 9x-8=22+7x | | 6x-7=x-42 | | x+y(1-q)=y+x(1-q) | | 5x-7+6x+6=27 | | 24+6x=3x+42 | | 18xy-9x^2y^2= | | 10x-13=6x+35 | | 42x^3+36x^2-6= | | 3x+7=x+27 | | 3x+71=10x-13 | | w-6=16+2 |